2014
DOI: 10.1111/mmi.12639
|View full text |Cite
|
Sign up to set email alerts
|

The Leishmania donovani chaperone cyclophilin 40 is essential for intracellular infection independent of its stage‐specific phosphorylation status

Abstract: SummaryDuring its life cycle, the protozoan pathogen Leishmania donovani is exposed to contrasting environments inside insect vector and vertebrate host, to which the parasite must adapt for extra-and intracellular survival. Combining null mutant analysis with phosphorylation site-specific mutagenesis and functional complementation we genetically tested the requirement of the L. donovani chaperone cyclophilin 40 (LdCyP40) for infection. Targeted replacement of LdCyP40 had no effect on parasite viability, axeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 68 publications
(104 reference statements)
0
25
0
Order By: Relevance
“…cyp40 −/− null mutant parasites were generated as previously described by sequential replacement of the endogenous CYP40 alleles using two targeting constructs comprising puromycin and bleomycin resistance genes flanked by approximately 1,000 bp of the 5′ and 3′UTRs of the L. infantum CYP40 gene (GeneDB accession number LinJ.35.4830; Yau et al. ). For genetic complement of cyp40 −/− null mutants, a cyp40 −/− /+ “add‐back” line was established using a knock in strategy integrating the CyP40 ORF and 3′UTR into the ribosomal locus (Yau et al.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…cyp40 −/− null mutant parasites were generated as previously described by sequential replacement of the endogenous CYP40 alleles using two targeting constructs comprising puromycin and bleomycin resistance genes flanked by approximately 1,000 bp of the 5′ and 3′UTRs of the L. infantum CYP40 gene (GeneDB accession number LinJ.35.4830; Yau et al. ). For genetic complement of cyp40 −/− null mutants, a cyp40 −/− /+ “add‐back” line was established using a knock in strategy integrating the CyP40 ORF and 3′UTR into the ribosomal locus (Yau et al.…”
Section: Methodsmentioning
confidence: 99%
“…For genetic complement of cyp40 −/− null mutants, a cyp40 −/− /+ “add‐back” line was established using a knock in strategy integrating the CyP40 ORF and 3′UTR into the ribosomal locus (Yau et al. ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A putative co-chaperone protein, cyclophilin 40 (CyP40), is a true virulence factor since it is essential both for the formation of the infective, metacyclic promastigote and for the parasite's establishment within macrophages [117]. The mechanisms by which CyP40 exerts its effects on metacyclogenesis and on intracellular survival are still in the dark.…”
Section: The Heat Shock Proteinsmentioning
confidence: 99%
“…In contrast to the FKBP subfamily that bind the immunosuppressive macrolide FK506, CyP40 belongs to the cyclophilin subfamily and binds the cyclic undecapeptide cyclosporine A. CyP40 is not recovered with native GR and MR, but with PR and ER [37,164,165]. Because CyP40 is also known to form complexes with dynein/dynactin [60] and associates to the cytoskeleton [166], it is entirely possible that this TPRdomain IMM plays a redundant role with FKBP52 and FKBPL/WisP39 in receptor trafficking. It has been shown that CyP40 is overexpressed in breast cancer tissues when it is compared to normal breast tissue [139] and also that the breast cancer cell line MCF-7 shows 75-fold higher level of Cyp40 mRNA expression in response to high temperature stress and a marked redistribution of Cyp40 protein from a predominantly nucleolar location to nuclear accumulation [167].…”
Section: Tpr-domain Immunophilins In Cancermentioning
confidence: 99%